Systematic Literature Review on Organizational and Financial Resilience - Juan Diego Ochoa Crespo; Jose Manuel Feria-Dominguez; Diego Marcelo Cordero Guzman (IEEE Access)
Organizational and financial resilience have emerged as crucial topics for the sustainability of SMEs, particularly in emerging economies where organizations face uncertain and volatile environments. This study presents a systematic literature review (SLR) to evaluate the current state of research on organizational and financial resilience in SMEs. Fifty-one primary studies published between 2000 and 2023 were reviewed, using strict inclusion and quality evaluation criteria to ensure the relevance and robustness of the findings. The results revealed that only 5.88% of the evaluated studies rigorously followed SLR guidelines, highlighting the scarcity of comprehensive reviews in this field. This review also underscores that organizational resilience, encompassing both planned and adaptive dimensions, is essential for SMEs to respond effectively to financial and operational crises. However, few studies have focused specifically on the Ecuadorian context, indicating a gap in the literature that should be addressed more thoroughly. This study concludes that future research should adopt more holistic approaches that incorporate both qualitative and quantitative methodologies to develop models that strengthen resilience among SMEs. Future studies should consider applying more rigorous SLR guidelines to improve research quality in this field.